Recurrent Afebrile Episodes of Spontaneous Pneumothorax in a Child with Well Controlled Systemic Lupus Erythematosus Disease - Mehta, Sudhir (Journal of Nepal Paediatric Society, 2016)
Systemic Lupus Erythematosus is an autoimmune disorder with multiple system involvement. Despite its pleuro-pulmonary involvement, recurrent spontaneous pneumothoraces are rare complication of childhood SLE. We report a 12 year old girl having SLE with nephritis, who developed recurrent episodes of spontaneous pneumothoraces. Surgical management with prolonged evacuation and aggressive immunosuppressive therapy improves the outcome for these patients. J Nepal Paediatr Soc 2016;36(1):94-96.